ANALISIS PENGARUH COMPRESSOR WASHING TERHADAP EFISIENSI KOMPRESOR DAN EFISIENSI THERMAL TURBIN GAS BLOK 1.1 PLTG UP MUARA TAWAR - Bambang Setiawan; Gunawan Hidayat (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
Muara Tawar Gas Turbine Power Plant is one of the generating units in Indonesia. Combined Cycle Power Plant is a plant that has a fast response to load changes. Therefore changes in the load on the combined cycle often occurs. To keep performance at combined cycle power plant, existing equipment must be maintained in a condition PLTGU order to work optimally. At this final project will be analysis the effect compessor washing to compressor efficiency and gas turbine eficiency of gas turbine combine cycle power plant block 1.1 UP Muara by analyzing the resulting efficiency compressor and gas turbine. From the results of this study found that the highest compressor efficiency of gas before compressor washing is 0.31% and after compressor washing is 0.53 %. Highest Thermal efficiency before compressor washing is 0.039% and after compressor washing is 1.461%.